Organizational antecedents and capabilities and their effects on firm competitiveness of sustainable supply chain management: An empirical evaluation in a developing economy - Chacón Vargas, Jairo Raúl; Moreno Mantilla, Carlos Eduardo (Escuela Colombiana de Ingeniería Julio Garavito, 2017)
Drawing from the Resource-Based View and Stakeholder theories, this article aims to evaluate empirically the relationship between organizational antecedents, firm capabilities for Sustainable Supply Chain Management (SSCM), and the latter’s effects on competitive advantage for a group of 126 focal firms in the city of Bogotá, Colombia. A mixed methods research design was followed. A self-administered (online) questionnaire was sent to a convenience sample of firms. The validity and reliability of the theoretical constructs were verified through validated factors modeled using reflective indicators, and the structural equation model was tested using partial least squares (PLS). Along with internal consistency, convergent and discriminant validities of the measurement model were evaluated. Finally, the constructs of organizational antecedents, SSCM practices and their effects on the focal company’s competitive advantage appear to be properly in line with the data collected and the testing of the proposed framework has provided an acceptable fit with positive relationships between the factors involved.

A partir de la visión basada en recursos y las teorías de las partes interesadas, este artículo tiene como objetivo evaluar empíricamente la relación entre los antecedentes organizacionales, las capacidades de las empresas para la gestión sostenible de la cadena de suministro (SSCM) y los efectos de estas últimas sobre la ventaja competitiva para un grupo de 126 empresas focales en el ciudad de Bogotá, Colombia. Se siguió un diseño de investigación de métodos mixtos. Se envió un cuestionario autoadministrado (en línea) a una muestra de empresas de conveniencia. La validez y confiabilidad de los constructos teóricos se verificaron a través de factores validados modelados usando indicadores reflexivos, y el modelo de ecuaciones estructurales se probó usando mínimos cuadrados parciales (PLS). Junto con la consistencia interna, se evaluaron las validezes convergente y discriminante del modelo de medida. Finalmente, las construcciones de los antecedentes organizacionales, las prácticas de SSCM y sus efectos en la ventaja competitiva de la empresa focal parecen estar adecuadamente en línea con los datos recopilados y la prueba del marco propuesto ha proporcionado un ajuste aceptable con relaciones positivas entre los factores involucrados.
Keywords: Cadena de valor; Value chain; Cadena de valor empresarial; Business value chain; Competencia económica; Competition; Economía - Bogotá; Economy - Bogota; Desarrollo económico; Economic development